Gambaran Kesehatan Mental Emosional Remaja - Florensa, Florensa; Hidayah, Nurul; Sari, Lintang; Yousrihatin, Fajar; Litaqia, Wulida (Jurnal Kesehatan, 2023)
Adolescence is the period from children to adulthood. This has an impact on various mental health problems in adolescents such as emotional mental problems, problems with parents and friends, anxiety and depression so that it is necessary to identify adolescent mental health problems through early detection. The research aims to identify the emotional mental health status of adolescents. Data were analyzed by descriptive analysis. The population and sample of this study were 478 junior high school students in Pontianak City. The data collection tool used the Strength and Difficult Questionnaire-SDQ. The results showed that the majority of adolescents had normal behavior problems (62.1%), normal emotional problems (92.9%), normal peer problems (54.4%), and normal prosocial abilities (83.5%). The results of this study can be used as a basis for developing activities to improve and prevent adolescent mental health problems.